Physical Work Capacity of Young Greco-Roman Wrestlers on the Background of their Somatic Development (Baltic Journal of Sport and Health Sciences, 2018)
On the basis of studies of 210 Greco-Roman wrestlers aged 11—18 the impact of training loads and sports selectionin the above sports event upon physical development and general work capacity of young athletes have beendetermined.Besides, age dynamics of changes of the major somatic indices (body length and mass) as well as physical workcapacity at the stage of initial and basic sports preparation has been determined.The studies have resulted in the determination of specific for Greco-Roman wrestlers changes in the examined indicesand development of evaluation scale of general physical work capacity.On the basis of findings we may conclude that Greco-Roman wrestling has a positive influence on developing body.In most cases mean values of examined somatic indices exceed those of children not engaged in sports as well aschildren practising other sports events. This sports event may be considered as a good means stimulating physicaldevelopment of children and youth.The age of 11—15 has turned to be the period of the greatest structural and functional changes in their ontogenesis.During this period the greatest rate of development is peculiar for body mass and height (11—12 years — mass 16%,length 6%; 14—15 years — mass 25%, length 6%), whereas development of work capacity occurs evenly. Along withrelative stabilization of the rate of body mass and height development beginning from the age of 16 high rate of workcapacity development is observed.Keywords: Greco-Roman wrestling, somatic development, performance abilities.